PERIODE-LUMINISITAS CEPHEID DAN KOREKSI BOLOMETRIK BINTANG DERET UTAMA : METODOLOGI DAN HASIL - Avivah Yamani.R; S. Siregar (Lembaga Penerbangan dan Antariksa Nasional, 2006)
Chepeids variable stars define as istance candle, espicially for local galaxies. In this paper, we derive Luminosity-Period relation. We estimate the model base on distribution pattern of Mv versus log P, Primary data taken from Storm et, al. (2004). Least squares methods being use to estimate regression coefficients. In our work, we find Mv = -2.83 log P-1.3 for Galactic Chepeids and Mv = -6.69 log P + 3.38 for Small Magellan Cloud. We discuss the factors that make the gradient separation with previous results. Bolometric correction we use here are from the main sequence stars (Cox, 2000). We use least squares method to fit while regression correction estimate with Cramer method. Regression equation that we have is : BC = -8.96(log Teff)2 + 70.23 logTeff - 137.83